First-principles investigations of Na2CuMCl6 (M = Bi, Sb) double perovskite semiconductors: Materials for green technology. (1st November 2022) - Al-Qaisi, Samah; Mushtaq, Muhammad; Alomairy, Sultan; Vu, Tuan V.; Rached, Habib; Haq, Bakhtiar Ul; Mahmood, Q.; Al-Buriahi, M.S.
Abstract: Investigations of stable lead-free perovskites have ignited an increasing interest in overcoming lead-based perovskites' instability and toxicity problems. This study thoroughly investigated the transport, nature of electronic, stability, and optical properties of inorganic halide double perovskites', namely Na2 CuMCl6 (M = Bi, Sb), to better understand their possible applications. The theory of density function was applied to determine the physical characteristics of these materials. This cubic material's stability was validated by optimizing the mechanical stability test, tolerance factor, and structure. Small bandgap semiconductors with outstanding optoelectronic performance caused by low reflectivity, high conductivity, and optical absorption, as well as a high potential for optoelectronic application, were used. Due to the small bandgap, we also identified multiple transport parameters with chemical potential (μ). Based on this study, our findings revealed that the figure of merit (ZT) was near to unity due to the semiconducting nature of the materials, implying that it will be effective in thermoelectric technology.